2007
DOI: 10.1007/s00464-007-9462-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colorectal resection does not reduce incisional hernia rates when compared with open colorectal resection

Abstract: Laparoscopic colorectal resection does not appear to reduce incisional hernia rates when compared with open surgery. Large randomised trials are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 16 publications
3
46
0
2
Order By: Relevance
“…Similar negative findings have been reported by others. 20, 21 We have not analyzed the risk factors for wound-related complications in our study, but our data have clearly indicated that the laparoscopic approach with smaller wounds is not always associated with lower rates of wound infection and incisional hernia.…”
Section: Discussionmentioning
confidence: 99%
“…Similar negative findings have been reported by others. 20, 21 We have not analyzed the risk factors for wound-related complications in our study, but our data have clearly indicated that the laparoscopic approach with smaller wounds is not always associated with lower rates of wound infection and incisional hernia.…”
Section: Discussionmentioning
confidence: 99%
“…However, a mini-laparotomy is needed for specimen extraction, which may be the main reason for postoperative pain, wound infection, and incisional hernia in conventional laparoscopy [5][6][7]. Thus, development of less invasive methods by reducing the number and size of abdominal incisions represents a new tendency in surgical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, long-term data demonstrate that the incisional hernia rate is similar after laparoscopic and open colorectal resections. 9,10 Although there have been several reports in the literature looking at the incisional hernia rate after laparoscopic and open colorectal resections, there are relatively few studies investigating the possible association of site of specimen extraction and development of incisional hernias. The aim of this study was therefore to evaluate the effect of different extraction sites on the incisional hernia rate in laparoscopic colorectal resections.…”
mentioning
confidence: 99%